Characteristics of Analog Rice From Potato Flour (Solanum tuberosom L.) Corn Flour (Zea mays L.) and Sago Flour (Arenga microcarpa Beccari) - Korompis, Olga S.; Mamuaja, Christine F.; Mandey, Lucia C. (Jurnal Ilmu dan Teknologi Pangan, 2016)
Potato (Solanum tuberosum L.), corn (Zea mays L.) and sago (Arenga microcarpa Beccari) are crops containing high carbohydrate, as source of calory food, and those can be made into rice analog. This study aimed: (1) to determine the formulations by organoleptic test in manufacture analog rice from potato flour, corn flour and sago flour, and (2) to analyze the physical properties, chemical properties of rice analog from potato flour with the addition of corn flour and sago flour. The research began with the manufacture of potato flour, corn flour and sago flour, and then the manufacture of rice analog. The experiment used a completely randomized design with 4 treatments and 3 replications. Organoleptic test results and statistical analysis indicating the most preferred formula was the combination of 50% potato flour + 25% corn flour + 25% sago flour. Based on the physical and chemical analysis it obtained the best formulations of the analog rice was combination of 50% potato flour + 25% corn flour + 25% sago flour. The results of the study it concluded from the organoleptic test, physical and chemical analysis that the best analog rice was formula of 50% potato + 25% corn + 25% sago. These formulation provided good nutritional value based on the physical and chemical characteristics of rice analog that was easier to digest. Keywords: analog rice, organoleptic, physical properties, chemical properties